2018
DOI: 10.1080/08897077.2018.1439799
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Addiction Medicine Teaching through Functional Mentoring by Co-Training Generalist Chief Residents with Faculty Mentors

Abstract: Co-training generalist chief residents with a faculty mentor appeared to facilitate functional mentoring-driven Teaching Project implementation but did not further increase already high levels of other addiction medicine teaching. Faculty mentors with more years of teaching experience were more effective in facilitating Teaching Project implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Innovative methods like co-training with general physicians can facilitate mentorship programmes in such centres. The mentoring need is now even greater with the expansion of addiction medicine as a specialty and many young professionals joining their respective training programmes (11,34,35). Most of the study participants reported there are limited research opportunities for ECAMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative methods like co-training with general physicians can facilitate mentorship programmes in such centres. The mentoring need is now even greater with the expansion of addiction medicine as a specialty and many young professionals joining their respective training programmes (11,34,35). Most of the study participants reported there are limited research opportunities for ECAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the need and scope for research opportunities exclusively for ECAMPs will inform policymakers regarding various issues and challenges. Quality mentoring and strategic planning, along with a favorable environment, are some of the elements that should be combined to create a successful career in research (11). Moreover, there is a need to assess deficiencies in training, research interest, and need for mentoring among early-career addiction professionals and address important issues that may help them in career development to mid-career.…”
Section: Introductionmentioning
confidence: 99%
“…Specific training on screening and diagnosis of OUD and the use of medications for OUD were emphasized. Curriculum content was rooted in several chief resident experiences with an immersive program to teach addiction medicine [26]. All office staff including certified medical assistants, medical office assistants, and administrators received a one-time one-hour interactive session on the basic pathophysiology, assessment, and treatment of OUD led by a DATA-waivered faculty member prior to the OBOT clinic roll-out.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing array of resources available for medical providers who are interested in gaining knowledge and skills in addiction treatment, short of completing a fellowship. Immersion programs for residents, chief residents, fellows, and junior faculty that include longitudinal mentorship from Addiction Medicine specialists provide opportunities to build and disseminate knowledge and skills related to Addiction Medicine within academic settings [ 47 , 57 – 59 ]. Multiple web-based resources are available including the ASAM Fundamentals of Addiction Medicine Course, the SUD 101 Core Curriculum through the Providers Clinical Support System supported by the Substance Abuse and Mental Health Services Administration, the Addiction Treatment: Clinical Skills for Healthcare Providers course offered by addiction medicine experts at Yale University through Coursera, and the Michigan Collaborative Addiction Resources and Education System [ 60 – 63 ].…”
Section: Additional Resources For Gaining Addiction Medicine Knowledg...mentioning
confidence: 99%